Botanophilia in Eighteenth-Century France - Williams, R.L. author. aut Link
V, 197 p.
Keywords: The book describes the innovations that enabled botany, in the Eighteenth century, to emerge as an independent science, independent from medicine and herbalism. This encompassed the development of a reliable system for plant classification and the invention of a nomenclature that could be universally applied and understood. The key that enabled Linnaeus to devise his classification system was the discovery of the sexuality of plants. The book, which is intended for the educated general reader, proceeds to illustrate how many aspects of French life were permeated by this revolution in botany between about 1760 to 1815, a botanophilia sometimes inflated into botanomania. The reader should emerge with a clearer understanding of what the Enlightenment actually was in contrast to some popular second-hand ideas today.